2016
DOI: 10.1016/j.ygcen.2016.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Integrative and comparative reproductive biology: From alligators to xenobiotics

Abstract: Dr. Louis J. Guillette Jr. thought of himself as a reproductive biologist. However, his interest in reproductive biology transcended organ systems, life history stages, species, and environmental contexts. His integrative and collaborative nature led to diverse and fascinating research projects conducted all over the world. He doesn’t leave us with a single legacy. Instead, he entrusts us with several. The purpose of this review is to highlight those legacies, in both breadth and diversity, and to illustrate D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 119 publications
(146 reference statements)
0
4
0
Order By: Relevance
“…A cross-sectional, in-person study conducted in three CRGC-partnered communities was used as a case study for this critical reflection. McCoy et al (2016) authored a tribute to and a review of the scientific legacy of the late Dr. Louis J. Guillette Jr. and his work as a reproductive biologist. After eight interviews with CHWs who were involved with the study, Lesen et al (2019) recommended that (1) disaster resilience studies should involve the community as much as possible, as those communities often see the research as valuable; (2) during the development phase, researchers should consult with community partners to avoid cultural conflict and obtain feedback on recruitment and research methodologies; (3) cultural norms and communication methods should be incorporated into researcher-participant interactions; (4) community partners should be consulted when deciding how to disseminate results to the community; and (5) incorporating critical reflection and considerations of power dynamics in communities that have disaster history can empower community members and researchers by promoting ethically and socially just resilience research (Lesen et al, 2019).…”
Section: Disaster Planning and Responsementioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional, in-person study conducted in three CRGC-partnered communities was used as a case study for this critical reflection. McCoy et al (2016) authored a tribute to and a review of the scientific legacy of the late Dr. Louis J. Guillette Jr. and his work as a reproductive biologist. After eight interviews with CHWs who were involved with the study, Lesen et al (2019) recommended that (1) disaster resilience studies should involve the community as much as possible, as those communities often see the research as valuable; (2) during the development phase, researchers should consult with community partners to avoid cultural conflict and obtain feedback on recruitment and research methodologies; (3) cultural norms and communication methods should be incorporated into researcher-participant interactions; (4) community partners should be consulted when deciding how to disseminate results to the community; and (5) incorporating critical reflection and considerations of power dynamics in communities that have disaster history can empower community members and researchers by promoting ethically and socially just resilience research (Lesen et al, 2019).…”
Section: Disaster Planning and Responsementioning
confidence: 99%
“…After eight interviews with CHWs who were involved with the study, Lesen et al (2019) recommended that (1) disaster resilience studies should involve the community as much as possible, as those communities often see the research as valuable; (2) during the development phase, researchers should consult with community partners to avoid cultural conflict and obtain feedback on recruitment and research methodologies; (3) cultural norms and communication methods should be incorporated into researcher-participant interactions; (4) community partners should be consulted when deciding how to disseminate results to the community; and (5) incorporating critical reflection and considerations of power dynamics in communities that have disaster history can empower community members and researchers by promoting ethically and socially just resilience research (Lesen et al, 2019). McCoy et al (2016) authored a tribute to and a review of the scientific legacy of the late Dr. Louis J. Guillette Jr. and his work as a reproductive biologist. Dr. Guillette was an internationally recognized leader in comparative reproductive biology and impacts of endocrine disrupting chemicals to both animals and humans, with prominent works including temperature-dependent sex determination of reptiles.…”
Section: Geohealthmentioning
confidence: 99%
“…Each of these manifestations of testicular dysgenesis syndrome have been linked to exposure to endocrine disrupting chemicals (EDCs) (Bay et al, 2006). Copious studies across taxa have found a diversity of reproductive effects induced by EDC exposure (Edwards et al, 2006; Lambert et al, 2015; McCoy et al, 2016; Skelly et al, 2010; Yeung et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Late Dr. Louis J. Guillette Jr. initiated investigations into xenobiotic effects on crocodilian species in the early 1990s [McCoy et al, 2016] in response to reports that juvenile populations of Alligator mississippiensis had declined in Lake Apopka (FL, USA) in the 1980s [Woodward et al, 1993]. The population decline in Lake Apopka was negatively associated with pesticide contamination, such as dicofol, containing 15% DDT and its metabolites, DDE [Clark, 1990].…”
mentioning
confidence: 99%